The Political Economy of Targeted Safety Nets - Ouerghi, Azedine (World Bank, Washington, DC, 2012)
To be successful, Social Safety Net (SSN) programs require three elements of policy design: technical correctness, administrative feasibility and political viability; yet the politically supportable aspect is often neglected. In this note, several features of political economy applicable to the choice, design, and implementation of safety net programs are discussed: modeling the electoral politics of targeting; the roles of attitudes and perceptions; centralized versus localized control; internal and organizational politics, and finally, politics and the different social objectives of safety ropes and safety nets. The note discusses the political viability of any SSN program, profoundly influenced by corruption and the perceptions of horizontal equity, process and administrative fairness, and effectiveness. Corruption subverts all three perceptions, and so is especially damaging to political support. Moreover, changes in the average poverty rate mask enormous "churning" as households move in and out of poverty. This volatility creates the demand not just for transfer programs to those whose incomes are chronically low (safety nets), but also for insurance-like programs that would pay off not only when income was absolutely low, but also when households experienced negative shocks (safety ropes). While safety "nets" seek to minimize income or expenditure poverty, the objective of safety "ropes" is to mitigate risk. If the targeting of social programs is judged exclusively on poverty or benefit incidence based on a cross sectional snapshot, then risk mitigation programs benefiting households who have suffered large shocks, but who are not "poor" may appear to have large "leakage" when in fact they are simply serving an alternative social objective. While a "safety net" program might be more popular, the more effectively it transfers from richer to poorer households, a "safety rope" program might cause little net redistribution, but be popular because it serves an important insurance function.